Environmental handbook for building and civil engineering projects checklists, obligations, good practice and sources of information - Venables, Roger (CIRIA special publication, 1994)
This handbook provides practical advice and guidance on the environmental issues that are likely to be encountered at each stage of a building or civil engineering project.